Task-Based E-Learning on Students’ Cognitive Assonance and Reading Engagement in English Learning Process at Elementary Schools - Sudatha, I Gde Wawan; Jayanti, Luh Sri Surya Wisma; Bayu, Gede Wira; Widiana, I Wayan; Halili, Siti Hajar Binti (International Journal of Language Education, 2024)
AbstractElementary school students still need help learning English, resulting in low learning outcomes. The lack of learning facilities and the application of inappropriate learning models impact students' low motivation to learn English. Regarding this matter, this study aims to examine the effectiveness of task-based e-learning on students' cognitive dissonance and reading engagement in learning English at elementary schools. The study was designed in a Quasi-Experimental Design with a posttest-only control group design. The population of the study was 158 4th-grade elementary school students. A random sampling technique was used in this study with a sample size of 55 4th-grade elementary school students. A survey was used to collect the data. The instrument used to collect research data was a questionnaire sheet. Two-way ANOVA was used to test the hypothesis. The results of the study show a significant effect simultaneously and partially with a Sig. value < 0.05, task-based e-learning has an impact on students' cognitive dissonance and reading engagement in learning English at elementary schools. The study implies that applying task-based e-learning can make it easier for students to learn English, which impacts their cognitive dissonance and reading engagement.